VEHICLE DETECTION AND COUNTING BERBASIS OTOMATIS MENGGUNAKAN YOLO - Juan Mora Michael Marbun; Panca Mudjirahardjo; n/a Soeprapto (Jurnal Mahasiswa TEUB, 2023)
Vehicle counting is considered as one of the most important applications in traffic control and management, for detection and counting of vehicles must be carried out. Efficient real time vehicle counting can improve control in traffic management by aiming to efficiently collect real time traffic information. In vehicle detection and counting system, vehicle detection and counting is very important for traffic flow in monitoring, planning and control. Traffic flow is monitored using a computer vision paradigm, where images or sequences of images provide improvements to the road view that are used to detect vehicles, monitor and count the number of vehicles in traffic flow. The system works by capturing video streams such as vehicles in the monitored area to compute information and transferring compressed video streams to provide a video based solution which is mainly implemented in OpenCV by Python Programming and using You Only Look Once (YOLO) is an approach for real-time object detection based on a Convolutional Neural Network. Keywords: Vehicle Detection and Counting, Open-Cv, Phyton, Yolo DAFTAR PUSTAKA[1] Undang-Undang No 22 Tahun 2009 Tentang Lalu Lintas Dan Angkutan Jalan.[2] Yustianingsih, H. & Istianah. (2013). Survei Kepadatan Arus Lalu Lintas Di Persimpangan Penceng Jalan Ra. Rukmini, Kecapi Kebupaten Jepara. Reviews In Civil Engineering. Jepara: Universitas Islam Nahdlatul Ulama.[3] TRIBUNJOGJA. (2020). Masih Menghitung Kendaraan Secara Manual, Dishub DIY Butuh Alat yang Lebih Canggih Masih Menghitung Kendaraan Secara Manual, Dishub DIY Butuh Alat yang Lebih Canggih (jogjaprov.go.id). (diakses 21 Oktober 2022).[4] Pamudi. (2018). Penerapan Sistem Dinamik Dalam Sistem Transportasi Cerdas Untuk Mengurangi Kemacetan, Polusi DanMeningkatkan Keselamatan Berlalu Lintas (Study Kasus Dinas Perhubungan Kota Surabaya). Surabaya: Institut Teknologi Sepuluh Nopember Surabaya[5] Yostisa, R. (2021). Penerapan Sistem Transportasi Cerdas Di Ibu Kota Negara Baru https://baketrans.dephub.go.id/berita/penerapan-sistem-transportasi-cerdas-di-ibukota-negarabaru~Intelligent%20Transport%20 System%20atau%20sistem,transportasi%2C%20kendaraan%20dan%20pengguna%20jalan. (diakses 21 Oktober 2022)[6] Najm, M. & Ali, Y. H. (2020). Automatic Vehicles Detection, Classification and Counting Techniques / Survey. Department of Computer Science. Iraq: University of Technology, Baghdad[7] Redmon, J., Divvala, S., Girshick, R. & Farhadi, A. (2016). You only look once: Unified, realtime object Detection. Proceedings of the IEEE Computer Society Conference on Computer Vision and Pattern Recognition. https://doi.org/10.110 9/CVPR.2016.91. (diakses 26 Oktober 2022)[8] Amwin, A. (2021). Deteksi dan Klasifikasi Kendaraan Berbasis Algoritma You Only Look Once (YOLO) Program Studi Informatika. Yogyakarta: Program Sarjana Fakultas Teknologi Industri Universitas Islam Indonesia